Horticultural innovation by viral-induced gene regulation of carotenogenesis. Issue 1 (18th January 2022) - Paudel, Lucky; Kerr, Stephanie; Prentis, Peter; Tanurdžić, Miloš; Papanicolaou, Alexie; Plett, Jonathan M; Cazzonelli, Christopher I
Abstract: Multipartite viral vectors provide a simple, inexpensive and effective biotechnological tool to transiently manipulate (i.e. reduce or increase) gene expression in planta and characterise the function of genetic traits. The development of virus-induced gene regulation (VIGR) systems usually involve the targeted silencing or overexpression of genes involved in pigment biosynthesis or degradation in plastids, thereby providing rapid visual assessment of success in establishing RNA- or DNA-based VIGR systems in planta . Carotenoids pigments provide plant tissues with an array of yellow, orange, and pinkish-red colours. VIGR-induced transient manipulation of carotenoid-related gene expression has advanced our understanding of carotenoid biosynthesis, regulation, accumulation and degradation, as well as plastid signalling processes. In this review, we describe mechanisms of VIGR, the importance of carotenoids as visual markers of technology development, and knowledge gained through manipulating carotenogenesis in model plants as well as horticultural crops not always amenable to transgenic approaches. We outline how VIGR can be utilised in plants to fast-track the characterisation of gene function(s), accelerate fruit tree breeding programs, edit genomes, and biofortify plant products enriched in carotenoid micronutrients for horticultural innovation.